2010
DOI: 10.1099/ijs.0.014308-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Photorhabdus and Xenorhabdus based on universally conserved protein-coding sequences and implications for the taxonomy of these two genera. Proposal of new taxa: X. vietnamensis sp. nov., P. luminescens subsp. caribbeanensis subsp. nov., P. luminescens subsp. hainanensis subsp. nov., P. temperata subsp. khanii subsp. nov., P. temperata subsp. tasmaniensis subsp. nov., and the reclassification of P. luminescens subsp. thracensis as P. temperata subsp. thracensis comb. nov.

Abstract: We used the information from a set of concatenated sequences from four genes (recA, gyrB, dnaN and gltX) to investigate the phylogeny of the genera Photorhabdus and Xenorhabdus (entomopathogenic bacteria associated with nematodes of the genera Heterorhabditis and Steinernema, respectively). The robustness of the phylogenetic tree obtained by this multigene approach was significantly better than that of the tree obtained by a single gene approach. The comparison of the topologies of single gene phylogenetic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
125
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 42 publications
4
125
0
1
Order By: Relevance
“…Biolog GN microplate reactions indicated that strain SF87 T utilized N-acetylglucosamine, DL-lactic acid, bromosuccinic , Kuwata et al (2012), Lengyel et al (2005), Nishimura et al (1994), Somvanshi et al (2006), Tailliez et al (2006Tailliez et al ( , 2010Tailliez et al ( , 2012 and Thomas & Poinar (1979). +, Carbohydrate utilized; 2, not utilized; W, weak reaction; V, variable reaction.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Biolog GN microplate reactions indicated that strain SF87 T utilized N-acetylglucosamine, DL-lactic acid, bromosuccinic , Kuwata et al (2012), Lengyel et al (2005), Nishimura et al (1994), Somvanshi et al (2006), Tailliez et al (2006Tailliez et al ( , 2010Tailliez et al ( , 2012 and Thomas & Poinar (1979). +, Carbohydrate utilized; 2, not utilized; W, weak reaction; V, variable reaction.…”
mentioning
confidence: 99%
“…Lee & Stock (2010) analysed the 16S rRNA gene and two housekeeping genes, phosphoserine aminotransferase and recA, while Tailliez et al (2010Tailliez et al ( , 2012 and Kuwata et al (2013) used the genes recA, dnaN, gltX, gyrB and infB. In this study, partial recA, dnaN, gltX, gyrB and infB gene sequences of strains SF87 T , SF80, SF362 and 106-C were analysed using the neighbour-joining method.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…caribbeanensis and Photorhabdus luminescens subsp. hainanensis (Tailliez et al, 2010), Photorhabdus luminescens subsp. kayaii (Hazir et al, 2004), Photorhabdus luminescens subsp.…”
mentioning
confidence: 99%